Improving the Attractiveness of Waste Steel Cans for Steel Mills by Removing Tin - B.J. Gajda; J. Reterski (Archives of Foundry Engineering)
The ever-increasing amount of municipal waste due to the rising demand for consumer goods presents a significant challenge in finding new, effective methods for material recovery and recycling. A considerable proportion of these materials are steel cans made of tin-coated steel sheets. Tin, being a metal with broad applications and limited natural resources, should be recovered from waste materials. Recovering/removing tin from waste steel cans would make them a more attractive raw material for steel mills. Processes for recovering tin from the surface of steel sheets in used cans mainly rely on hydrometallurgical methods. This paper presents the results of tin recovery from steel sheets using leaching with a 1M NaOH solution at 90°C. Tests were conducted on the removal of paint and varnish layers that inhibit the tin removal process. The results show that it is possible to improve the efficiency of tin recovery from cans through chemical treatment, which will significantly increase steel mills' interest in this type of waste as a valuable input for metallurgical processes and a source of iron. Closing the loop in a closed circuit involved the electrolysis of tin from the leaching solution.